Piaget's developmental theory formal reasoning patterns [videorecording] - Piaget, Jean 1896-1980 (Davidson Films, 1976)
Shows tasks that challenge the thinking of secondary school students, including tasks which involve proportional reasoning, separation of variables, combinational logic, and the integration of these in an analysis of a balanced beam with weights. Illustrates the tasks Dr. Piaget developed to probe the thinking styles of secondary students.